Chemical and semisynthesis of modified histones. (18th January 2016) - Maity, Suman Kumar; Jbara, Muhammad; Brik, Ashraf
Abstract : Post‐translational modifications (PTMs) of histones play critical roles in the epigenetic regulation of eukaryotic genome by directly altering the biophysical properties of chromatin or by recruiting effector proteins. The large number of PTMs and the inherent complexity in their population and signaling processes make it highly challenging to understand epigenetics‐related processes. To address these challenges, accesses to homogeneously modified histones are obligatory. Over the last decade, synthetic protein chemists have been devising novel synthetic tools and applying state‐of‐the‐art chemoselective ligation strategies to prepare precious materials useful in answering fundamental questions in this area. In this short review, we cover some of the recent breakthroughs in these directions in particular the synthesis and semi‐synthesis of modified histones and their use to unravel the mysteries of epigenetics. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Post‐translational modifications of histones play critical roles in the epigenetic regulation of eukaryotic genome, which is very challenging to understand. This review focuses on the recent attempts to address these challenges by using chemically and semisynthetically prepared modified histones.